Implementasi Model Problem Based Learning (PBL) Berbasis Eksperimen Untuk Meningkatkan Aktivitas Belajar Peserta Didik Pada Materi Getaran Di SMP - Juniar Afrida; Nengsih, Sri; Saifiyaturramah, Saifiyaturramah (Al-Khazini, 2022)
The learning model becomes an important factor when the learning process is carried out because the learning model is a plan that helps based on the continuity of the learning process and can be implemented in accordance with the learning objectives. So it is necessary to apply an experimental-based problem besed learning (PBL) learning model to increase students’ learning activitieson vibration material. This study aims to (1) apply the experimental-based problem-based learning (PBL) learning model to improve student learning activities (2) find out the results of observations obtained through the experimental-based problem based learning, learning model. The research method used is the experimental research method (the Non-Equivalent Group Design). The results obtained from three observers are in the experimental class the average score for implementation =89%, Reaction =89% and activity = 84% with a very active category. While in the control class the average score for implementation =53% reaction 55% and activity 51% with the less active category. So it can be said that the application of the experimental-based learning model can improve the learning activities of students on vibration material at SMP Negeri 1 Simpang Ulim.